Climate risk perceptions of businesses: The role of experience and objective risk factors - Markus Rieger-Fels (Institut für Mittelstandsforschung (IfM) Bonn, 2025)
The changing climate requires businesses to take adaptive action. A key prerequisite for optimal adaptive action is that businesses are aware of the climate risks that they face. This, in turn, necessitates that businesses do not base their risk perception solely on prior experience, or a lack thereof, but take objective risk factors into account. I use data from a large-scale survey of German businesses to investigate how they assess the acute physical climate risk presented by the increased frequency of natural hazards: droughts, storms, extreme heat, heavy precipitation, and floods. I find experience to have a large effect on the perceived probability of hazard events, but no effect on their perceived consequences. Objective risk criteria such as firm size, industry, and location characteristics inform expectations independent of experience and, depending on the hazard, even to a larger extent than experience. The results suggest that it might not be a lack of risk awareness that underlies any adaptation gap. – – Auf Basis von Daten einer großen Befragung deutscher Unternehmen wird untersucht, wie Unternehmen das physische Klimarisiko durch häufiger werdende Naturgefahren einschätzen: Dürren, Stürme, Extremhitze, Starkniederschläge und Hochwasser. Die Ergebnisse zeigen, dass Erfahrungen mit Klimarisiken einen starken Einfluss auf die wahrgenommene Wahrscheinlichkeit, aber keinen Einfluss auf die erwartete Konsequenz von Schadensereignissen hat. Objektive Risikofaktoren, wie Unternehmensgröße, Branche und lokale Gegebenheiten des Unternehmensstandorts beeinflussen die Erwartungen der Unternehmen, unabhängig von und zum Teil in stärkeren Maß als Erfahrungen mit Klimarisiken.
Keywords: D22; D83; Q54; 330; Risk perception; risk management; climate risks; natural hazards